IMPLEMENTASI EVALUASI PEMBELAJARAN OLEH DOSEN PRODI PENDIDIKAN AGAMA KRISTEN DI STT KRISTUS ALFA OMEGA SEMARANG SEMESTER GANJIL TA 2018/2019 - Susilo, David Priyo (Sekolah Tinggi Teologi Kristus Alfa Omega, 2018)
One of the duties of the lecturer is to evaluate learning. Lecturers who conduct evaluations of learning well will encourage students to have self-confidence, improve achievement and have hopes of achieving the future. Lecturers as good evaluators have a big impact on students. Evaluation of good learning is done through a good process. First, the measurement is preceded by marking using numbers that are learned by using tests to measure cognitive aspects and using non-tests to measure affective and psychomotor aspects and then interpreting and evaluating. Second, an assessment is carried out, namely the interpretation of the measurement results, for example students who have a value of 90 are included in the good. Evaluation of learning, namely the provision of data based on measurement and assessment.So the method used in this study is descriptive research method about the Implementation of Learning Evaluation by Lecturers at STT Kristus Alfa Omega Semarang This Odd Semester 2018/2019 Academic Year wants to know the level of learning evaluation conducted by lecturers of Christian Education study programs at STT Kristus Alfa Omega Semarang without making comparisons or relationships with other variables.The sound of the first hypothesis is thus, the sound of the first hypothesis is the level of the expected level of implementation of learning evaluation by the lecturer of odd semester Christian Education Education Study Program 2018/2019 in STT Kristus Alfa Omega Semarang in the medium category equal to 60% of the maximum value not accepted .Based on the results of the research item which states